ANALISIS KETERAMPILAN BERPIKIR KRITIS PADA MODEL PEMBELAJARAN BERBASIS MASALAH DAN PEMBELAJARAN INKUIRI - Worachak, Sam Phoen; Damnoen, Phrapalad Somchai; Hong, Dong Anh Chi; Putri, Sabila Eka (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2023)
This study is the first to conduct a literature review of the ability to think critically in problem-based learning and inquiry learning models in physics education. The method used is qualitative research with a literature review system. This research data collection technique uses secondary data, namely relevant research articles. The process of reviewing articles in this study focuses on problem-based learning and inquiry learning models that can improve students’ critical thinking skills in physics concepts and phenomena. The instruments used in data collection included reviewing scientific articles sourced from Google Scholar with the criteria for selected articles according to search keywords and selected articles published within the last 10 years and analyzed using a synthesis matrix. From the literature study that has been carried out, the researcher found as many as 25 articles regarding problem-based learning and inquiry learning models that can improve students’ critical thinking skills in physics education. With these learning models, students’ low critical thinking skills in physics learning can be increased and students understand physics learning better. The novelty of this study is that it provides a comprehensive and systematic overview of the existing literature on the effectiveness of problem-based learning and inquiry learning models in enhancing students’ critical thinking skills in physics education. The implications of this study are that it can inform teachers, curriculum developers, and policymakers on how to design and implement problem-based learning and inquiry learning models in physics education to foster students’ critical thinking skills and learning outcomes.